Pentingnya Pendidikan Agama Islam bagi Orang Tua dalam Mendidik Anak - Saeful Azis (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2018)
The purpose of this paper is to emphasize the importance of parents' knowledge of Islamic religious education in educating their children. Islamic religious education is a process in which there is a transfer of knowledge about Islam by educators to students in order to prepare students to believe, understand, and practice Islamic teachings. Educators in this paper are parents, namely fathers and mothers who have the responsibility to educate, nurture and guide their children (students) so that their children will become children who can draw closer to Allah SWT (worship) and have noble character (akhlak al-karimah). One of the characteristics of children is imitative. Psychologists assume that in all cases children are accomplished imitators. This copycat character is a positive capital in religious education in children. The emergence of the nature of imitating it requires a model to be emulated. Therefore, educators, especially parents, must make themselves as models or good examples (uswah Hashanah) for their children. The importance of knowledge about Islamic religious education for parents in educating their children is something that should not be underestimated by parents as the main educators for their children. If parents do not have knowledge about Islamic religious education, of course, parents will not be able to become educators, leaders, role models or models that their children will emulate.